A inclusão no mundo do trabalho das mulheres técnicas em eletromecânica egressas do IFS - Campus Lagarto - Pereira, Telma Amélia de Souza (2023)
Professional education at the Federal Institutes of Education, Science and Technology is a possibility of qualification for the population. The occupation of vacancies by women/girls is shown to be disproportionate in numbers of admission and completion of courses, making it difficult to participate in the field of industry, an area historically organized based on patriarchal elements. This research analyzes the experiences of women who graduated from the technical course of Integrated High School in Electromechanics at the Campus Lagarto of the Federal Institute of Sergipe, highlighting difficulties and advances in gender relations in professional training and in the world of work. The investigation is guided by presuppositions of historicaldialectical materialism, feminist and gender theories, focusing on categories of gender analysis, sexual division of labor and professional education. Methodologically, the research presents a qualitative character, of the 'case study' type, integrating in the analysis the general and particular, micro and macro, objective and subjective, individual and collective, academic community, institution, government policies and experiences of women who graduated from IFS - Lagarto Campus of the Integrated High School Technical Course in Electromechanics. The oral sources are part of 30 semi-structured interviews with women who graduated from the technical course in question, consisting of direct contact and adopting the snowball methodology or “Snowball” strategy to contact more respondents. The insertion of the researcher in the daily life of the institution subsidized the observation and interaction to capture unique aspects and intervening factors of reality. Documentary sources are part of the literature review; the school record on personal data of graduates of 11 classes in the time frame between 2009 and 2020; electronic sources for mapping the State of the Art or production of knowledge in the field of education. The Content Analysis (CA) method is the methodological proposal for the treatment of data, allowing to identify what is behind the empirically observed reality, the meaning attributed by the subjects to the addressed themes. In the study, it was observed that the option of the graduates for the Electromechanics course is justified by the search for the quality of the institution's teaching in the region, by indication of family members and/or friends. The difficulty in accessing the work area was evident in practical activities during the course, later, in the search for an internship, mobilizing part of the women for other areas of activity or higher education. The participation of women increases in schooling and occupation of job vacancies, however, women technicians reveal access barriers in the industrial area, demarcating the need for greater valuation in technical courses and in the world of work. The discredit of women in the labor market and the social division of roles between men and women are consequences of a socio-historical process marked by different determinants in each society, and, particularly in Brazil, by the way in which the construction of the country was structured with the influence of the patriarchal system and violent colonization.